Peningkatan Keterampilan Bercerita Siswa Setelah Menggunakan Media Animasi Audio Visual Dongeng Binatang Berbasis Canva - Setiyaningsih, Suci; Yuwana, Setya; Hendratno (Jurnal Elementaria Edukasia, 2023)
Storytelling is one of the language skills that must be mastered by students. Storytelling skills refer to the ability to tell stories as a component of Indonesian language proficiency. Storytelling skills are language skills by conveying the contents of the story through speech. However, it was found that the students' storytelling skills were still in the low category. This study aims to determine the effect of canva-based animal fairy tales audio-visual animation learning media on students' storytelling skills. The research design used in this research is experimental research with pre-test and post-test data measurements. The sample used in this study was grade II students at SD Taman Sidoarjo using a saturated sample technique so that it used the entire population, so that the total sample in this study was 17 students. The results of the Wilcoxon Signed Ranks test found that P 0.000 < 0.05, this shows that there is a difference in effect between the pre and post tests. There is a significant influence of Canva-based audio-visual animation learning media on improving the storytelling skills of grade II elementary school students